Pelatihan Kompetensi Guru untuk Meningkatkan Proses Pembelajaran Inovatif dan Kreatif di Yayasan Iskariman - Saroni, M.; Araniri , Nuruddin; Nahriyah , Syafa’atun (JURNAL PARAHITA ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
Teachers or educators are professional jobs, and they are required to have several separate competencies to support the realization of quality, effective and efficient education and achieve learning goals. In carrying out learning, many still use conventional learning methods, many use only the lecture method, which can result in students becoming bored in learning, there is a need to develop interesting learning media. This Community Service Method uses training and workshop activities for educators at the Iskariman Foundation institution by providing understanding and mentoring. Based on the results and discussion of the results of these activities, it can be concluded: 1) This training and workshop activity provides an understanding of implementation in planning, implementing and evaluating learning that is student-centered, focuses on abilities, and supports the development of students' character. 2) In assisting educators in adapting technology, especially in assisting learning activities, it can help educators in integrating learning into social media platforms. 3) Educators receive direct guidance in making innovative and creative teaching materials by making information technology-based learning media.